Pemberdayaan Petani Kopi Manggarai Timur melalui Optimisasi Pemasaran Berbasis Website Interaktif - Teddy Mantoro; Ben Rahman; Aris Gunaryati; Mohammad Iwan Wahyuddin; Abdul Rahman Wijaya Putra; Andryana, Septi (PELITA NUSA TENGGARA, 2025)
Indonesia is one of the world's leading coffee producers, offering a wide variety of flavors and characteristics across its regions, including the eastern part of the archipelago. One promising area is Rende Nao Village, located in Lamba Leda Timur District, East Manggarai Regency, which is known for its Colol coffee. Despite its high quality and strong market potential, the use of digital media for marketing remains limited. The East Manggarai Coffee Farmers Association (ASNIKOM) has established an official website; however, low levels of digital literacy and ineffective content management hinder efforts to expand market reach and build a strong digital product identity. In response to these challenges, this community engagement program was conducted to introduce the concept of an interactive website as an initial strategy to enhance the digital marketing capacity of local coffee farmers. The program employed a participatory and educational approach, involving discussions, needs assessments, and demonstrations of basic website features. Rather than focusing on advanced technical training, the initiative emphasized conceptual understanding and content planning based on local input. As a result, the program increased awareness of the potential of digital marketing and led to the development of an initial strategy for ASNIKOM’s website, laying the foundation for strengthening farmers’ digital competencies as an adaptive step toward sustainable and technology-based coffee marketing practices.